The Relationship of ST Segment Changes in Lead aVR with Outcomes after Myocardial Infarction; a Cross Sectional Study - Beyranvand, Mohammad Reza; Assadpour Piranfar, Mohammad; Mobini, Mohammadreza; Pishgahi, Mehdi (Archives of Academic Emergency Medicine, 2017)
Introduction: Among the 12 leads studied in electrocardiography (ECG), lead aVR can be considered as the most forgotten part of it since no attention is paid to it as the mirror image of other leads. Therefore, the present study has been designed with the aim of evaluating the prevalence of ST segment changes in lead aVR and its relationship with the outcome of these patients. Methods: In this retrospective cross sectional study medical profiles of patients who had presented to emergency department with the final diagnosis of myocardial infarction (MI) in a 4-year period were evaluated regarding changes of ST segment in lead aVR and its relationship with in-hospital mortality, the number of vessels involved, infarct location and cardiac ejection fraction. Results: 288 patients with the mean age of 59.00 ± 13.14 (18 – 91) were evaluated (79.2% male). 168 (58.3%) patients had the mentioned changes (79.2% male). There was no significant relationship between presence of ST changes in lead aVR with infarct location (p = 0.976), number of vessels involved (p = 0.269) and ejection fraction on admission (p = 0.801). However, ST elevation ≥ 1 mv in lead aVR had a significant relationship with mortality (Odds = 7.72, 95% CI: 3.07 – 19.42, p < 0.001). Sensitivity, specificity, positive and negative predictive values and positive and negative likelihood ratios of ST elevation ≥ 1 for prediction of in-hospital mortality were 41.66 (95% CI: 22.79 – 63.05), 91.53 (95% CI: 87.29 – 94.50), 31.25 (95% CI: 16.74 – 50.13), 94.44 (95% CI: 90.65 – 96.81), 0.45 (95% CI: 0.25 – 0.79), and 0.05 (95% CI: 0.03 – 0.09), respectively. Conclusion: Based on the results of the present study, the prevalence of ST segment changes in lead aVR was estimated to be 58.3%. There was no significant relationship between these changes and the number of vessels involved in angiography, infarct location and cardiac ejection fraction. However, presence of ST elevation ≥ 1 in lead aVR was associated with 8 times increase in in-hospital mortality risk.